Characterization and Potential of Plant Growth-Promoting Rhizobacteria (PGPR) Isolates Capacity Correlating with Their Hydrocarbon Biodegradation Capability - Pujawati Suryatmana; Mieke Rochimi Setiawati; Diyan Herdiyantoro; Betty Natalie Fitriatin; Nadia Nuraniya Kamaluddin (AGRIVITA, Journal of Agricultural Science, 2022)
The aim of this research is to find the characteristics of three PGPR isolates—Azospirillum sp., Bacillus sp., and Pseudomonas sp.: First, by profiling their characteristics in a liquid bioremediation system and secondly by measuring their performance as a bioagent in a soil phytoremediation system using ramie plant (Boehmia niviea L.). A Randomized Block Design in triplicate is used: (1) a Nitrogenfree medium with mineral media containing 1% (wt/v) petroleum hydrocarbons; and (2) 1% (wt/v) glucose medium as control. We tested their petroleum-degrading capacity, nitrogenase activity, phytohormones production, and ramie plant growth. The results showed that both Pseudomonas sp. (98.7%, 81.78% degradation efficiency) and Azospirillum sp. (93.80%, 83.70%) were the superior candidate in both systems. They both show reduced but adequate phytohormone production, managing to improve ramie plant growth. Both also showed reduced but sufficient nitrogen fixing capabilities to improve hydrocarbon degradation activity effectively. Meanwhile, Bacillus sp. has the lowest biodegradation capabilities (84.07%; 78.6%) and lowest nitrogenase activity, while failing to improve plant growth. Therefore Bacillus sp. would be more beneficial in a bacterial consortium where its characteristics (high IAA production) can be coupled with other isolates that can offset its lack of phytohormone or nitrogenase activity.